BCL‐XL binds and antagonizes RASSF6 tumor suppressor to suppress p53 expression. (28th November 2017) - Xu, Xiaoyin; Iwasa, Hiroaki; Hossain, Shakhawoat; Sarkar, Aradhan; Maruyama, Junichi; Arimoto‐Matsuzaki, Kyoko; Hata, Yutaka
Abstract : RASSF6, a member of the tumor suppressor Ras‐association domain family proteins, induces apoptosis in the caspase‐dependent and caspase‐independent manners. RASSF6 interacts with MDM2 and stabilizes p53. BCL‐XL is a prosurvival member of BCL‐2 family proteins. BCL‐XL directly inhibits proapoptotic BAX and BAK. BCL‐XL also traps tBID, a proapoptotic activator BH3‐only protein, and sequesters p53. In addition, BCL‐XL regulates the mitochondrial membrane permeability via voltage‐dependent anion channel. In these manners, BCL‐XL plays an antiapoptotic role. We report the interaction of BCL‐XL with RASSF6. BCL‐XL inhibits the interaction between RASSF6 and MDM2 and suppresses p53 expression. Consequently, BCL‐XL antagonizes RASSF6‐mediated apoptosis. Thus, the inhibition of RASSF6‐mediated apoptosis also underlies the prosurvival role of BCL‐XL. Abstract : RASSF6 blocks MDM2‐mediated p53 degradation and induces apoptosis. BCL‐XL inhibits the interaction between RASSF6 and MDM2 and plays a prosurvival role.